EFFECTIVENESS AND INNOVATION OF PROBLEM-BASED LEARNING IN PHYSICS LEARNING IN A DECADE: A LITERATURE ANALYSIS OF CRITICAL THINKING DEVELOPMENT - Harahap, Rofiqoh Hasan; Sudarma, Teguh Febri; Novika, Sutri; Festiyed, Festiyed (Universitas Labuhanbatu, 2025)
Purpose – This study examines the effectiveness of the PBL model in enhancing students' CTS in physics education. It explores recent innovations, including digital learning tools, authentic assessment, and local cultural contexts.Methodology—This study uses a Systematic Literature Review (SLR) approach, guided by the PRISMA framework, to review 18 peer-reviewed articles published between 2014 and 2024. These studies focus on the impact of PBL on students' CTS in physics education.Findings – The findings show that PBL consistently improves students' CTS, with N-Gain values ranging from moderate to high (0.36–0.73). PBL outperformed models like Discovery Learning, Reciprocal Learning, and Demonstration Methods, though the OR-IPA model performed better in some contexts, fostering higher-order thinking skills (HOTS). Innovations in PBL materials, such as worksheets, modules, E-LKPD, PhET simulations, and interactive multimedia, demonstrated high validity (0.82–0.93) and effectiveness in supporting Learning. PhET simulations and interactive multimedia helped students understand abstract physics concepts and enhanced critical thinking.Contribution—This study highlights the importance of integrating technology, local wisdom, and web-based Learning in PBL to enhance its effectiveness. It also provides practical recommendations for educators, including developing technology-based materials, teacher training, and improved access to learning resources like computers and the Internet